Frequency independent microstrip stacked antenna - Kumar Sharma S.; Vishvakarma B.R. (My University, 2025)
The advancement of technological development in the microstrip antenna and its applications in diverse areas, have given rise to the need for a frequency agile and frequency independent microstrip antenna which could be used for the same range of frequencies without altering the system. Requirements of such nature could be met by log periodic antenna. However, in the present endeavour a frequency independent microstrip stacked antenna consisting of nine elements operating in the S-band (2.000-4.000 GHz) has been proposed. The developed antenna has been experimentally tested over an achievable band of frequencies from 3.200 to 3.920 GHz. The antenna performance has characteristics like E-plane radiation patterns. The 3 dB beamwidth, radiated power and VSWR show very similar behaviour for the different frequencies of operation obtainable in the S-band. The coaxial-fed microstrip stacked antenna provides an operational bandwidth of approximately 23%, i.e. 3.200 GHz to 3.920 GHz. The VSWR for the entire operational band is around 2 whereas the gain for the antenna is found to vary from 4.00 to 8.36 dB. The 3 dB beamwidth has been found to fluctuate between 16.8° and 23.5°. The designed antenna can be well suited for the practical broadband applications.